Two decades of research on Borrelia burgdorferi sensu lato in questing Ixodes ricinus ticks in Slovakia - Rusňáková Tarageľová, Veronika; Derdáková, Markéta; Selyemová, Diana; Chvostáč, Michal; Mangová, Barbara; Didyk, Yuliya M.; Koči, Juraj; Kolenčík, Stanislav; Víchová, Bronislava; Peťko, Branislav; Stanko, Michal; Kazimírová, Mária (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionIn Europe, Borrelia burgdorferi sensu lato (s.l.), the causative agent of Lyme borreliosis is transmitted by the castor bean tick, Ixodes ricinus. In the last decades, global changes affect the spread of ticks and also their bionomics. The aim of this study was summarization of a large dataset obtained during 20 years of research.MethodsThe research was carried out in 1999-2019 at 16 localities in Slovakia that were continuously monitored. In total, 17,249 questing I. ricinus ticks were tested for the presence of B. burgdorferi s.l. ResultsThe total prevalence of infected ticks was 18.8% (3,248/17,249), with 15.1% (1,557/10,302) infected nymphs and 24.3% (1,691/6,947) infected adults. Nine species of B. burgdorferi s.l. were identified. Borrelia afzelii (37.1%), B. garinii/bavariensis (24.7%), and B. valaisiana (15.4%) were the most frequent and were present at all study sites, followed by B. lusitaniae (12.6%), B. burgdorferi sensu stricto (4.1%) and B. spielmanii (1.6%). Borrelia bavariensis was confirmed only in four samples (0.1%), however, detection of this species has been performed only since 2017. Borrelia bissettii and B. kurtenbachii were both recorded in one case. The total prevalence differed significantly among four habitat types (urban, suburban, natural, agricultural). The highest infection prevalence was confirmed in natural habitat (22.0%), the lowest in urban habitat (13.2%). In addition, molecular analysis was carried out on part of the collected ticks previously morphologically identified as I. ricinus. The analysis did not confirm the occurrence of Ixodes inopinatus in Slovakia.ConclusionLong-term monitoring of the abundance and spread of ticks as well as the prevalence and genetic variability of tick-borne pathogens can reveal the impact of global climatic and socio-economic changes on different habitats, including natural foci of tick-borne pathogens.